Uptake of breast and cervical cancer screening in four Gulf Cooperation Council countries. Issue 5 (September 2019) - So, Vivian H.T.; Channon, Andrew A.; Ali, Mohamed M.; Merdad, Leena; Al Sabahi, Sultana; Al Suwaidi, Huda; Al Ajeel, Abdullah; Osman, Nabil; Khoja, Tawfik A.M.
Abstract : In Gulf Cooperation Council States, there is limited information on national levels of mammography and Pap smear screening uptake. The aim of this study is to provide a baseline for national estimates for mammography and Pap smear screening and to explore associations between screening uptake and socioeconomic factors. The nationally representative World Health Survey Plus, implemented in 2008/2009 in Kuwait, Oman, Saudi Arabia and United Arab Emirates (UAE), was used. Uptake of mammography and Pap smear was estimated for each country, followed by the examination of associations between screening and a range of socioeconomic variables. Levels of breast and cervical cancer screening uptake within recommended intervals in all countries were low. The percentages of women aged 40–75 years who had a mammogram were 4.9% in Saudi Arabia, 8.9% in Oman, 13.9% in the UAE and 14.6% in Kuwait. The percentages of women aged 25–49 years who had a Pap smear test were 7.6% in Saudi Arabia, 10.6% in Oman, 17.7% in Kuwait and 28.0% in the UAE. Marital status, wealth, education, nationality and place of residence are associated with screening uptake, with the lower educated, poor and unmarried having the lowest percentages of uptake. The four Gulf Cooperation Council countries need to set clear targets and increase the proportion of women who have regular breast and cervical cancer screening examinations. Health education campaigns and awareness programmes that are fully integrated into the health system are required to ensure women use services that are available to prevent breast and cervical cancers.